Pengaruh Leverage dan Profitabilitas Terhadap Pengungkapan Corporate Social Responsibility - Rivandi, Muhammad; Dewi, Mike Kusuma; Meirina, Elsa (Faculty of Economic and Business, 2021)
Management of natural resources and environment who is not responsible the main issues disclosure of corporate social responsibility . This study aims to determine the influence of leverage and profitability on the disclosure of corporate social responsibility. The company sampled 42 high profile companies selected using purposive sampling techniques. The hypothesis testing process is done using panel regression. Based on the test results found that leverage is insignificant to CSR disclosure, while profitability has a significant positive influence on CSR disclosure. High profile Company is a company that has a high level of sensitivity to the environment. The company's operational activities are high profile potential and directly related to the environment. It is expected that for High Profile Company management in order to maintain and improve the company's performance, the greater the financial performance will increase CSR disclosure.Cara Mengutip:Rivandi, M., Dewi, M. K., & Meirina, E. (2021). Pengaruh Leverage dan Profitabilitas Terhadap Pengungkapan Corporate Social Responsibility. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.14249.